Utilization of Rumen Mechanical Stimulator as Pseudo Fiber in Ruminant to Minimize Metabolic Problem - Nurmeiliasari Nurmeiliasari; R Priyanto; D A Astuti; . Salundik; J Takahashi (Indonesian Center for Animal Research and Development, 2017)
Feeding high concentrate diet, characterized with high starch and low fiber is applied to increase energy intake for an optimal production performance in ruminants. However, the prevalence of digestive disorder namely ruminal acidosis has been reported as drawback of this feeding strategy. This encourages farmers and nutritionist to supply adequate fiber in the diet to meet minimum dietary fiber requirement. However, feeding high forage diet is reported to give adverse effect on production performance, thus economic loss for farmers. Therefore, some sorts of artificial fiber utilizations have been introduced to reduce the risk of nutritional diseases as well as improving ruminant productivity. The utilization of rumen mechanical stimulator aims to maintain a healthy rumen function in ruminants fed with high concentrate diet. Objective of this article is to review recent development of rumen mechanical stimulators utilization, a pseudo fiber to substitute forage physical function in the rumen of ruminants. This review highlights the use of rumen mechanical stimulators in dairy cattle, beef cattle and sheep with particular attention in rumination time and rumen parameters. In conclusion, rumen mechanical stimulator is attributable to minimize metabolic problem associated with high concentrate feeding by providing mechanical stimulation on the rumen wall.